Analisis Faktor-Faktor yang Memengaruhi Niat Beli pada Restoran Cepat Saji di Batam dengan Citra Merek Sebagai Variabel Mediasi - Fitra Akbar; Sunargo Sunargo (J-MAS (Jurnal Manajemen dan Sains), 2022)
A fast food restaurant can be referred to as a container or place that provides food or drink in a short and easy time. Fast food restaurants have developed a lot as evidenced by the number of outlets that increase every year, this happens because consumers or customers are very interested in buying food and drinks at fast food restaurants. The purpose of this study was to analyze the factors that influence purchase intention at fast food restaurants in Batam with brand image as a mediating variable. Sampling in this study used non probability sampling, namely the purposive sampling method by taking or selecting respondents who had certain characteristics. Tests were carried out using Smart PLS. The results of the study stated that the e-WOM variable on purchase intention with the mediation of brand image produced a positive and significant effect. Price on purchase intention with the mediation of brand image had a positive and significant effect.